Design strategy for nanostructured arrays of metallodielectric cuboids to systematically tune the optical response and eliminate spurious bulk effects in plasmonic biosensors - Grab, Anna Luise; Bacher, Andreas; Nesterov-Müller, Alexander; Dahint, Reiner (Bioengineering, 2022)
Plasmonic biosensors are a powerful tool for studying molecule adsorption label-free and with high sensitivity. Here, we present a systematic study on the optical properties of strictly regular nanostructures composed of metallodielectric cuboids with the aim to deliberately tune their optical response and improve their biosensing performance. In addition, the patterns were tested for their potential to eliminate spurious effects from sensor response, caused by refractive index changes in the bulk solution. Shifts in the plasmonic spectrum are exclusively caused by the adsorbing molecules. For this purpose, nanopatterns of interconnected and separated cubes with dimensions ranging from 150 to 600 nm have been fabricated from poly(methyl methacrylate) using electron-beam lithography followed by metallization with gold. It is shown that a small lateral pattern size, a high aspect ratio, and short connection lengths are favorable to generate extinction spectra with well-separated and pronounced peaks. Furthermore, for selected nanostructures, we have been able to identify reflection angles for which the influence of the bulk refractive index on the position of the plasmonic peaks is negligible. It is shown that sensor operation under these angles enables monitoring of in situ biomolecule adsorption with high sensitivity providing a promising tool for high-throughput applications.